2023
DOI: 10.3390/ani13203293
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Registered Milk Fat-to-Protein Ratio for the Assessment of Metabolic Status in Dairy Cows

Ramūnas Antanaitis,
Karina Džermeikaitė,
Vytautas Januškevičius
et al.

Abstract: This study endeavors to ascertain alterations in the in-line registered milk fat-to-protein ratio as a potential indicator for evaluating the metabolic status of dairy cows. Over the study period, farm visits occurred biweekly on consistent days, during which milk composition (specifically fat and protein) was measured using a BROLIS HerdLine in-line milk analyzer (Brolis Sensor Technology, Vilnius, Lithuania). Clinical examinations were performed at the same time as the farm visits. Blood was drawn into antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…In our previous study, we discovered that cows with higher milk lactose concentrations were significantly more active (increasing by 54.47%) and had a lower risk of developing subclinical acidosis (SARA), as demonstrated by a 2.52% increase in the reticulo-ruminal pH and a 9.86% extension in the rumination time [ 15 ]. Antanaitis et al [ 5 ] found that cows suffering from acidosis were less active compared to healthy ones. The definition of SARA based on rumen pH is subject to debate [ 31 ], but previous research [ 32 , 33 ] has shown that a rumen pH below 6 is indicative of SARA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we discovered that cows with higher milk lactose concentrations were significantly more active (increasing by 54.47%) and had a lower risk of developing subclinical acidosis (SARA), as demonstrated by a 2.52% increase in the reticulo-ruminal pH and a 9.86% extension in the rumination time [ 15 ]. Antanaitis et al [ 5 ] found that cows suffering from acidosis were less active compared to healthy ones. The definition of SARA based on rumen pH is subject to debate [ 31 ], but previous research [ 32 , 33 ] has shown that a rumen pH below 6 is indicative of SARA.…”
Section: Discussionmentioning
confidence: 99%
“…During each milking cycle, the analyzer continuously measures the composition of each cow’s milk. This ‘mini-spectroscope’ can be mounted on the milking stalls or on a milking robot in the milk line and requires no additional reagents or maintenance [ 5 ]. Milk serves as an ideal medium for assessing the health of dairy cows due to its non-invasive collection method and ease of access, making it a common tool for detecting ketosis and other issues related to production [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure the model's applicability and adaptability to different management practices and diets, it is essential to incorporate and evaluate additional data from various farms before its practical implementation [21]. Recently, technologies that record behavior have become commercially accessible, paving the way for advancements in precision cattle husbandry [22]. The daily milk fat-to-protein ratios of cows can be measured using a BROLIS HerdLine in-line milk analyzer (Brolis Sensor Technology, Vilnius, Lithuania).…”
Section: Introductionmentioning
confidence: 99%
“…Before the model is put into operation, further data from other farms must be incorporated and assessed in order to guarantee that it is applicable to a variety of management styles and dietary requirements [21]. A BROLIS HerdLine in-line milk analyzer (Brolis Sensor Technology, Vilnius, Lithuania) can be used to measure the daily milk fat-to-protein ratios of cows [22]. Understanding the relationships between these features in food, blood, and milk can assist in understanding the health and production status of animals.…”
Section: Introductionmentioning
confidence: 99%